Methodology used in comparative studies assessing programmes of transition from paediatrics to adult care programmes: a systematic review. Issue 1 (27th January 2017) - Le Roux, E; Mellerio, H; Guilmin-Crépon, S; Gottot, S; Jacquin, P; Boulkedid, R; Alberti, C
Abstract : Objective: To explore the methodologies employed in studies assessing transition of care interventions, with the aim of defining goals for the improvement of future studies. Design: Systematic review of comparative studies assessing transition to adult care interventions for young people with chronic conditions. Data sources: MEDLINE, EMBASE, ClinicalTrial.gov. Eligibility criteria for selecting studies: 2 reviewers screened comparative studies with experimental and quasi-experimental designs, published or registered before July 2015. Eligible studies evaluate transition interventions at least in part after transfer to adult care of young people with chronic conditions with at least one outcome assessed quantitatively. Results: 39 studies were reviewed, 26/39 (67%) published their final results and 13/39 (33%) were in progress. In 9 studies (9/39, 23%) comparisons were made between preintervention and postintervention in a single group. Randomised control groups were used in 9/39 (23%) studies. 2 (2/39, 5%) reported blinding strategies. Use of validated questionnaires was reported in 28% (11/39) of studies. In terms of reporting in published studies 15/26 (58%) did not report age at transfer, and 6/26 (23%) did not report the time of collection of each outcome. Conclusions: Few evaluative studies exist and their level of methodological quality is variable. The complexity of interventions, multiplicity of outcomes, difficulty of blinding and the small groups of patients have consequences on concluding on the effectiveness of interventions. The evaluation of the transition interventions requires an appropriate and common methodology which will provide access to a better level of evidence. We identified areas for improvement in terms of randomisation, recruitment and external validity, blinding, measurement validity, standardised assessment and reporting. Improvements will increase our capacity to determine effective interventions for transition care.